2013
DOI: 10.1111/gcb.12184
|View full text |Cite
|
Sign up to set email alerts
|

Climate change scenarios experiments predict a future reduction in small pelagic fish recruitment in the Humboldt Current system

Abstract: The Humboldt Current System (HCS) sustains the world's largest small pelagic fishery. While a cooling of this system has been observed during recent decades, there is debate about the potential impacts of rising atmospheric CO2 concentrations on upwelling dynamics and productivity. Recent studies suggest that under increased atmospheric CO2 scenarios the oceanic stratification may strongly increase and upwelling-favorable winds may remain nearly constant off Peru and increase off Chile. Here we investigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 80 publications
3
64
1
2
Order By: Relevance
“…This marine ecosystem is highly susceptible to changes in upwelling patterns, such as alteration in frequency or magnitude (Aravena et al 2014). Significant potential impacts due to climate change have been projected on the spawning rate of small pelagic fish, such as the Peruvian anchovy Engraulis ringens and the sardine Sardinops sagax (Brochier et al 2013), despite the projected temperatures remaining within accepted ecological ranges (Bertrand et al 2004). Small pelagic species strongly depend on zooplankton availability and the exceptional phytoplankton productivity in coastal upwelling zones .…”
Section: Considerations For Marine Life and Fishery Productivitymentioning
confidence: 99%
See 2 more Smart Citations
“…This marine ecosystem is highly susceptible to changes in upwelling patterns, such as alteration in frequency or magnitude (Aravena et al 2014). Significant potential impacts due to climate change have been projected on the spawning rate of small pelagic fish, such as the Peruvian anchovy Engraulis ringens and the sardine Sardinops sagax (Brochier et al 2013), despite the projected temperatures remaining within accepted ecological ranges (Bertrand et al 2004). Small pelagic species strongly depend on zooplankton availability and the exceptional phytoplankton productivity in coastal upwelling zones .…”
Section: Considerations For Marine Life and Fishery Productivitymentioning
confidence: 99%
“…In effect, the optimal environmental range for primary productivity in coastal marine ecosystems has been associated with moderate upwelling intensity (Cury and Roy 1989;Bakun et al 2015). Outcomes from a coupled physical-biochemical model by Brochier et al (2013) project decreasing nursery areas for small pelagic fish under extreme climate change in the Humboldt ecosystem.…”
Section: Considerations For Marine Life and Fishery Productivitymentioning
confidence: 99%
See 1 more Smart Citation
“…In the central California Current EBUS, Palacios et al (2004) estimated that stratification has increased since the 1950s in coastal and offshore areas. However, this change may reflect interdecadal variability (Bograd and Lynn, 2003;Chhak and Di Lorenzo, 2007), and its impacts on the nutrient input and consequent biological productivity have not been assessed except by theoretical modeling (Brochier et al, 2013;Schroeder et al, 2014). In other systems, similar studies are lacking due to the paucity of observational data on water-column temperature.…”
Section: Water Temperatures and The Counteracting Roles Of Upwelling mentioning
confidence: 99%
“…Nevertheless, a modeling study by Brochier et al (2013), based on downscaling of an AOGCM (Echevin et al, 2012), found that stratification might increase in the Humboldt Current under global climate change. In conjunction with negligible change in winds, their models showed limited nutrient input into the euphotic zone, which would negatively affect biological productivity.…”
Section: Water Temperatures and The Counteracting Roles Of Upwelling mentioning
confidence: 99%